Systematic Mapping Global Outsourcing: A Systematic Literature Review - Abdurokhim, Abdurokhim; Senen, Syamsul Hadi; Rofaida, Rofi (Budapest International Research and Critics University, 2022)
This paper is initial research that seeks to explore the results of previous studies in the field of global outsourcing using the Literature Systematic Review (LSR). The purpose of mapping with LSR is to find out what global outsourcing topics have been researched. The search was carried out on Scopus and Global Outsourcin google Scholar. A total of 6 global outsourcing articles published electronically, both in the form of scientific journals and conference proceedings, are included in the inclusion criteria. The results of this slr provide an overview of opportunities to explore new topics in global outsourcing or exploit existing topics. recommendations from this study include the need for more research on global outsourcing so that it can be used as a reference in the scientific development of human resources management; it is necessary to develop global outsourcing research in overcoming workers' problems; the development of new concepts and frameworks in global outsourcing still requires further study; studies on global outsourcing research objects need to be developed.